China’s community corrections: an actuarial model of punishment - Li, Enshen (Crime, law and social change, 2015)
This article examines the emergence and configuration of community corrections in China. It argues that the adoption of this new sanction is a result of China’s recent rhetorical shift in penality from harshness and punishment towards leniency and rehabilitation. Nevertheless, based on a study of community corrections in Shanghai, the practice of this sanction manifests strong evidence of actuarial justice in its form and function. The findings from this study show that community corrections are used in practice as a managerial tool to identify, classify and regulate offenders to control dangerousness they may present, and to facilitate the implementation of correctional programs. This actuarial model of practice is represented by the risk-driven, differentiated approaches in the exercise of community corrections and the cost-saving aim of handling offenders in the neighbourhood.